GRADASI BASIL TAHAN ASAM (BTA) POSITIF DENGAN RESIKO PENULARAN ANGGOTA KELUARGA DALAM SATU RUMAH (KONTAK SERUMAH ) PENDERITA TBC PARU - Rheegandono, Arief; Indasah, Indasah (STRADA : Jurnal Ilmiah Kesehatan, 2013)
The bad behavior of the people suffering from TB Paru BTA positive will be contagious to other people especially infection contact of the same home. To know whether there is relationship between The gradation of the people suffering TB Paru BTA positive and infection contact of the same home, analytical survey research has been done using cross sectional planning. The research population is the people with TB Paru degradation BTA positive suffering and the member of all families sufferer. The research variable is independent variable that is the positif degradation TB Paru and dependent variable that is the contact among the family members of the same home. The data analysis uses non parametric statistica with bi-variate test correlation / Spearman (rank correlation test). Significance test uses confidence interval (CI) : 95% and SPSS program for window version 17.00 The hypothesis is there is a correlation between the positive gradation of people suffering from TB Paru BTA positive and infection contact of the same home. The bi-variate analysis to variable, if p ≤ 0,05 so Ho is refused, it means there is correlation between the gradation of people suffering from TB Paru BTA positive and infection contact of the same home. The statistica test result is p = 0,00 or p ≤ 0,05 it means there is correlation between the gradation of people suffering from TB Paru BTA positive and infection contact of the same home.